If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -1) + 6(9x + -2) = 3(5x + -4) + 4 Reorder the terms: 4(-1 + 2x) + 6(9x + -2) = 3(5x + -4) + 4 (-1 * 4 + 2x * 4) + 6(9x + -2) = 3(5x + -4) + 4 (-4 + 8x) + 6(9x + -2) = 3(5x + -4) + 4 Reorder the terms: -4 + 8x + 6(-2 + 9x) = 3(5x + -4) + 4 -4 + 8x + (-2 * 6 + 9x * 6) = 3(5x + -4) + 4 -4 + 8x + (-12 + 54x) = 3(5x + -4) + 4 Reorder the terms: -4 + -12 + 8x + 54x = 3(5x + -4) + 4 Combine like terms: -4 + -12 = -16 -16 + 8x + 54x = 3(5x + -4) + 4 Combine like terms: 8x + 54x = 62x -16 + 62x = 3(5x + -4) + 4 Reorder the terms: -16 + 62x = 3(-4 + 5x) + 4 -16 + 62x = (-4 * 3 + 5x * 3) + 4 -16 + 62x = (-12 + 15x) + 4 Reorder the terms: -16 + 62x = -12 + 4 + 15x Combine like terms: -12 + 4 = -8 -16 + 62x = -8 + 15x Solving -16 + 62x = -8 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -16 + 62x + -15x = -8 + 15x + -15x Combine like terms: 62x + -15x = 47x -16 + 47x = -8 + 15x + -15x Combine like terms: 15x + -15x = 0 -16 + 47x = -8 + 0 -16 + 47x = -8 Add '16' to each side of the equation. -16 + 16 + 47x = -8 + 16 Combine like terms: -16 + 16 = 0 0 + 47x = -8 + 16 47x = -8 + 16 Combine like terms: -8 + 16 = 8 47x = 8 Divide each side by '47'. x = 0.170212766 Simplifying x = 0.170212766
| 8x-5(x+3)=(7x-1)3 | | 5y-8y-2=-41 | | 8y-6=2(4y+5) | | 6x+25=13x-59 | | 5x+6=-14x-13 | | 8x+7=2x+37 | | 5y=4x+5 | | 8x-2=66 | | 2x-3=x+1 | | 7x-9x=3(3x-7) | | 5+(3x-2)=18 | | 9x-25=4x+4 | | 4x+1=2x-4 | | 7x+-3+6y=32-4+2y | | 7x-7=x+5 | | 6.5X+3+2X=4X+15 | | 3(2x+1)=15 | | 3(4x+7)0=4x-25 | | 5x-16=x-4 | | 0-x=4 | | 2x=15+x | | 6h+3k-7(6h-4k)= | | 17-3x=-76 | | 4x+40+24y= | | 2y-4=20 | | 3w-12m+12=0 | | -2.25=1.5 | | 5x+30+55y= | | 2.1x-6.45=3.15-4.3x | | 4(x-6)+6=6(x+2)-8 | | 23x-9-12x+4=24x-4-13x+11 | | 5x+8-8x=17-18x+15x-9 |